Serum Lipid and Glycemic Profile in HARRT-Naïve and HARRT-Exposed HIV Patients in Enugu State, Nigeria: A Case–Control Study - Esther A. Ekwe; Birinus A. Ezeala-Adikaibe; Basden Onwubere; Julius Okoye; Collins Ugwu; Chidinma B. Nwatu; Ijoma Chinweuba; Chidimma Orah-Okpala; Raphael Anakwue; Oladipupo O. Fasa; Celestine C. Okwara; Uchechi Q. Arinze; et al. (International Journal of Medicine and Health Development)
Background: Although highly active antiretroviral therapy (HAART) has improved immunologic and virologic outcomes, as well as the quality of life of human immunodeficiency virus (HIV)-positive patients, it has worsened a wide range of metabolic derangements associated with HIV/AIDS. A wide range of lipid abnormalities and dysglycemia have been reported in patients on HARRT. Materials and Methods: The study was carried out at the University of Nigeria Teaching Hospital, a tertiary hospital in southeast Nigeria. A fasting venous blood sample was used to check for fasting plasma glucose. Results: Fasting blood glucose was significantly higher in HARRT-exposed individuals (P < 0.01). This is also true for total cholesterol and triglycerides (P < 0.01). High-density lipoprotein (HDL) was significantly higher in HAART-naïve individuals while low-density lipoprotein was higher in the control group. Comparing HAART-exposed patients and HAART-naïve patients, significantly more HAART-naïve patients had lower HDL (abnormal), P = 0.04, odds ratio = 1.57, 95% confidence interval, 1.01–2.45. HAART-naïve patients had higher rates of abnormal results, except for fasting plasma glucose. Conclusion: HAART-exposed and HAART-naïve HIV/AIDS patients have a high level of dyslipidemia compared with normal HIV-negative patients, and this effect is more pronounced in male patients than female patients. There should be increased surveillance for metabolic derangements in these patients at the time of diagnosis and recruitment into the HAART program. There is a need for the treatment of dyslipidemia in such patients.